Técnicas de fermentación del cacao CCN-51 y nacional usando la enzima pectin trans eliminasa como precursor sensorial de la almendra y licor de cacao - Lucero Álvarez, Mariela Gissela (2021)
The study was carried out at the “Cantos” and “Tierra Narvanda” farms, from January to April / 2020, in Buena Fé, Los Ríos, whose objective was to “Establish the effect of the enzyme Pectin trans eliminase on the physical characteristics of almonds and sensory attributes of the cocoa liquor of the CCN-51 and Nacional varieties”. The design was DCA of 8 postharvest treatments + 2 controls (conventional benefit) and 3 repetitions, adapted to the L8 (2) 7 orthogonal design (Taguchi methods). The CCN-51 and Nacional varieties were evaluated, as well as two levels for the factors: pre-benefit, enzyme dose, fermentation times, washing, post-washing rest and drying. The results showed that the immediate benefit of cocoa compared to the benefit after 72 hours of harvest showed a favorable effect on the weight of the almonds (difference of 6.1%), confidence of 99% (p> 0.01). The CCN-51 variety showed a higher seed index, with 1.77 g and the National cocoa had 1.42 g. The National cocoa, benefited at 72 hours, with a dose of 1 mL / 5 kg, fermentation for 30 minutes, drained, complete washing, post-wash rest and drying in a clothesline, allowed to have an average of well-fermented almonds (%) = 82.40 ± 0.70% > rest of treatments (p <0.05). In the sensory evaluation, significant differences were found in cocoa flavor (p <0.05) using enzymatic product 2 mL / 5 kg, drained, washed and post-washed. The content of polyphenols, theobromine and caffeine in treatment 7 was 69.75 mgAc Gallic / g, 1.97% and 0.41%, while in treatment 4 it was 78.21 mgAc Gallic / g 1.75% and 0.22%. The two treatments mainly present Oxomethyl acetate in its volatile compounds.